Age related reference ranges of respiratory rate and heart rate for children in South Africa. Issue 4 (6th January 2006) - Wallis, L A; Maconochie, I
Abstract : Background: The authors have recently presented reference ranges for heart rate and respiratory rate in healthy resting schoolchildren, aged 4–16 years, in the United Kingdom. There are no similar ranges for children in the developing world. Aims: To undertake a study in Cape Town, South Africa, to establish whether the UK ranges may be applied to socioeconomically disadvantaged groups. Methods: Data on 346 children in a township school were recorded; their height, weight, heart rate, and respiratory rate were compared to the UK ranges. Results: The two groups plotted closely together by height and weight on the UK 90 growth reference charts. There was no difference in heart rate between the two groups, and a difference of 0.46 breathes per minutes in respiratory rate, which is not felt to be of clinical significance. Conclusion: The reference rages of heart and respiratory rate derived in the UK may be applied to children in developing world situations.